Spermatogenesis and Cryptorchidism - Cobellis, Giovanni; Noviello, Carmine; Nino, Fabiano; Romano, Mercedes; Mariscoli, Francesca; Martino, Ascanio; Parmeggiani, Pio; Papparella, Alfonso (Frontiers in Endocrinology, 2014)
Cryptorchidism represents the most common endocrine disease in boys, with infertility more frequently observed in bilateral forms. It is also known that undescended testes, if untreated, lead to an increased risk of testicular tumors, usually seminomas, arising from mutant germ cells. In normal testes, germ cell development is an active process starting in the first months of life when the neonatal gonocytes transform into adult dark spermatogonia. These cells are now thought to be the stem cells useful to support spermatogenesis. Several researches suggest that adult dark spermatogonia form between 3 and 9 months of age. Not all the neonatal gonocytes transform into adult dark spermatogonia; indeed, the residual gonocytes undergo involution by apoptosis. In the undescended testes, these transformations are inhibited leading to a deficient pool of stem cells for post pubertal spermatogenesis. Early surgical intervention in infancy may allow the normal development of stem cells for spermatogenesis. Moreover it is very interesting to note that intra-tubular carcinoma in situ in the second and third decades have enzymatic markers similar to neonatal gonocytes suggesting that these cells fail transformation into adult dark spermatogonia and likely generate testicular cancer in cryptorchid men. Orchidopexy between 6 and 12 months of age is recommended to maximize the future fertility potential and decrease the testicular cancer risk in adulthood.